2018
DOI: 10.12788/jhm.2984
|View full text |Cite
|
Sign up to set email alerts
|

Things We Do For No Reason: Blood Cultures for Uncomplicated Skin and Soft Tissue Infections in Children

Abstract: Skin and soft tissue infections (SSTIs) are common pediatric diagnoses in both outpatient and inpatient settings. Blood cultures are frequently obtained for evaluation of SSTIs. Multiple studies have demonstrated that blood cultures rarely demonstrate true pathogenic bacterial growth, and even positive cultures do not change clinical management. Obtaining blood cultures has been associated with increased length of hospital stay. In addition, false-positive blood cultures may occur and result in repeat blood cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…MRSA detection can be performed on clinical isolates from several anatomical sites like wound exudates (pus), nasal swabs, skin swabs, and blood samples with nasal swabs being preferred by clinical test kits (40,41). However, the relevance of pus culture over other anatomic samples, especially blood, is recently reported in the literature with new tests being developed based on pus cultures (14,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…MRSA detection can be performed on clinical isolates from several anatomical sites like wound exudates (pus), nasal swabs, skin swabs, and blood samples with nasal swabs being preferred by clinical test kits (40,41). However, the relevance of pus culture over other anatomic samples, especially blood, is recently reported in the literature with new tests being developed based on pus cultures (14,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Among SSTI, despite the increasing prevalence of methicillin-resistant Staphylococcus aureus , evidence discourages routine collection of blood cultures in immunocompetent children. 11–14 For both CAP and SSTI, multiple studies have identified a higher rate of contaminants than true pathogens. 4,5,7,12 Finally, bacteremia infrequently occurs in children with UTI and, when identified, is nearly always identical to the urine culture isolate, signifying that blood cultures may represent a low-value test.…”
Section: Introductionmentioning
confidence: 99%
“…4 Overuse of BCx in uSSTIs has also been highlighted in the Journal of Hospital Medicine' s Choosing Wisely series: Things We Do For No Reason. 21 The value of CBC, CRP, 7 and ESR 22 has also come into question for uSSTIs because there is little published evidence demonstrating that these aid in diagnosis or management.…”
mentioning
confidence: 99%